2014
DOI: 10.2146/ajhp130200
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a pharmacist-supervised outpatient diabetes treatment clinic

Abstract: An outpatient clinic successfully integrated a pharmacist into a multidisciplinary PACT focused on veterans with poorly controlled type 2 diabetes. The clinic's initial experience suggests that frequent pharmacist interventions have a positive impact in promoting appropriate insulin use in this high-risk patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 22 publications
0
46
0
10
Order By: Relevance
“…Thus, telehealth patients’ glycemic control before baseline visits and afterward may have been better than that of patients who receive care only from primary care providers ( 17 ). However, use of midlevel providers such as pharmacists and nurses is common across the VA health system, is an integral part of the VA-established Patient Aligned Care Team model, and may represent the patient-centered care model in use ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, telehealth patients’ glycemic control before baseline visits and afterward may have been better than that of patients who receive care only from primary care providers ( 17 ). However, use of midlevel providers such as pharmacists and nurses is common across the VA health system, is an integral part of the VA-established Patient Aligned Care Team model, and may represent the patient-centered care model in use ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists were able to serve a more active role in the management of diabetic medications through initiating and adjusting both oral and injectable medications in these studies. [6][7][8][9][10] This study demonstrates the impact that pharmacists can have through management of only injectable diabetic medications. HbA 1c reductions were obtained through close monitoring and follow-up of glucose readings, conservative dosing guidelines and protocols, and direct pharmacist to patient interactions.…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that glycemic control in diabetics is very important for each patient. Several studies have demonstrated the benefit of glycemic control through pharmacist intervention [6][7][8][9][10]. This study originated as a way to justify pharmacist involvement with diabetes management.…”
mentioning
confidence: 99%
“…Such communication has been shown to improve patient outcomes and ensure quality of care for patients with chronic disease, which could help pharmacists and physicians improve their delivery of chronic pain management. 15,16 Among our respondents, the objective data of the K-TRACS report seemed to help physicians and pharmacists more readily discuss any concerns they might have had with both the patient as well as with each other. These discussions have validated prescription decisions, identified the need for abuse and addiction treatment, and in some instances, decreased prescription abuse and overprescribing.…”
Section: Discussionmentioning
confidence: 99%